Differences in lifestyle behaviors, dietary habits, and familial factors among normal-weight, overweight, and obese Chinese children and adolescents - Guo Xiaofan; Zheng Liqiang; Li Yang; Yu Shasha; Sun Guozhe; Yang Hongmei; Zhou Xinghu; Zhang Xingang; Sun Zhaoqing; Sun Yingxian (BMC, 2012)
Abstract Background Pediatric obesity has become a global public health problem. Data on the lifestyle behaviors, dietary habits, and familial factors of overweight and obese children and adolescents are limited. The present study aims to compare health-related factors among normal-weight, overweight, and obese Chinese children and adolescents. Methods We conducted a cross-sectional study consisted of 4262 children and adolescents aged 5-18 years old from rural areas of the northeast China. Anthropometric measurements and self-reported information on health-related variables, such as physical activities, sleep duration, dietary habits, family income, and recognition of weight status from the views of both children and parents, were collected by trained personnel. Results The prevalence rates of overweight and obesity were 15.3 and 6.4%, respectively. Compared to girls, boys were more commonly overweight (17.5% vs. 12.9%) and obese (9.5% vs. 3.1%). Approximately half of the parents with an overweight or obese child reported that they failed to recognize their child's excess weight status, and 65% of patients with an overweight child reported that they would not take measures to decrease their child's body weight. Obese children and adolescents were more likely to be nonsnackers [odds ratio (OR): 1.348; 95% confidence interval (CI): 1.039-1.748] and to have a family income of 2000 CNY or more per month (OR: 1.442; 95% CI: 1.045-1.99) and less likely to sleep longer (≥7.5 h) (OR: 0.475; 95% CI: 0.31-0.728) than the normal-weight participants. Conclusions Our study revealed a high prevalence of overweight and obesity in a large Chinese pediatric population. Differences in sleep duration, snacking, family income, and parental recognition of children's weight status among participants in different weight categories were observed, which should be considered when planning prevention and treatment programs for pediatric obesity.